Perancangan Aplikasi Quiz Sebagai Media Pembelajaran Sejarah - Idham Kholed Rachmawan; Enny Itje Sela (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Mastery of historical concepts is important for students in increasing their understanding of country’s past dan history. However, conventional history learning metodhs still often experience difficulties in attracting and motivating students to learn. Therefore, we need an interactive and fun learning media to increase students’ learning history. One alternative interactive learning media is an interactive quiz application. This study aims to help teachers in the learning process so that students are more interested in learning history with learning media in the form of interactive quiz applications. The interactive quiz application developed in this final project is an android-based application that makes it easier for students to learn history in a fun way. This application provides quizzes rellated to history subject matter wich are presented interactively. In addition, this application also provides an evaluation feature to evaluate students’ ability to master historical concepts.